Bronchiolitis obliterans organizing pneumonia: case report involving a differential diagnosis (Research, Society and Development, 2021)
Bronchiolitis obliterans organizing pneumonia (BOOP) is an entity with suggestive clinical and imaging diagnosis associated with evidence of connective tissue on the lumen of the distal air spaces at the lungs. Here we address a case of BOOP and highlight the importance of differential diagnosis. Male patient, 76 years old, ex-smoker (interrupted the habit about 30 years ago), developed complaints of copious and non-productive cough, thermometer fever of 38 ºC and weight loss without relief from the use of fenoterol + ipatropium bromide. There was no recent history of infection, use of systemic or inhaled drugs, or travel. He reported a relevant family history for cancer. Physical examination: patient conscious and comfortable, pale, acyanotic, anicteric, afebrile, eupneic and without signs of respiratory distress with Sat O2 = 98%. Percussion with clear pulmonary sound. Hissing auscultation in pulmonary bases and sparse snoring in the left hemithorax. Spirometric examination with normal parameters, with partial volume variation after the use of bronchodilator. The high-resolution computed tomography (HRCT) of the chest showed areas of consolidation in the alveolar air space, bilateral and asymmetric, with predominance in the peribronchial regions, some assuming the appearance of pulmonary nodules surrounded by ground glass. Later, in the differential diagnosis, positron emission tomography-computed tomography (PET-CT) revealed an inflammatory process in the resolving phase, ruling out other diseases, for example, pulmonary adenocarcinoma. We opted for the prescription of Prednisone and the follow-up of the condition with chest X-rays, which, after 4 months, showed patterns within the normal range. Currently, the patient is “well” and with total remission of symptoms and under continuous therapy.